2006
DOI: 10.1089/ten.2006.12.2343
|View full text |Cite
|
Sign up to set email alerts
|

High-Yield Isolation, Expansion, and Differentiation of Rat Bone Marrow–Derived Mesenchymal Stem Cells with Fibrin Microbeads

Abstract: Fibrin microbeads (FMB), made of extensively cross-linked dense and partially denatured fibrin, were used as a matrix for efficient isolation of mesenchymal stem cells (MSC) from rat bone marrow (BM). After 2 days of incubation of FMB with whole BM in suspension, a high number of cells of mesenchymal origin attached to the FMB. On the 14th day after their transfer to plastic, the yield of the cells isolated via FMB was approximately 3-4 times higher than that obtained by currently used protocols based solely o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 53 publications
1
62
0
Order By: Relevance
“…Therefore, we used FBS as the only source of growth factors for these cells. High yield MSC expansion on similar microbead carriers has been previously demonstrated for both rat 23,24 and human cells. 25,26 Unlike these prior reports, we expanded these cultures by adding media and microbead carriers, while retaining the nonadherent cellular fractions.…”
Section: Discussionmentioning
confidence: 85%
“…Therefore, we used FBS as the only source of growth factors for these cells. High yield MSC expansion on similar microbead carriers has been previously demonstrated for both rat 23,24 and human cells. 25,26 Unlike these prior reports, we expanded these cultures by adding media and microbead carriers, while retaining the nonadherent cellular fractions.…”
Section: Discussionmentioning
confidence: 85%
“…Made of extensively cross-linked and partially denatured fibrin, fibrin microbeads (FMBs) have been used to improve the biodegradability of matrices while retaining their high celladhesion properties. 97 In a typical procedure, FMBs are synthesized by oil-stirring of a fibrinogen and thrombin mixture at 65°C-75°C for 6-8 hours and stored as a dry powder. 98 At this high temperature, fibrinogen denatures while factor XIIIa can remain active and cross-link proteins.…”
Section: Different Forms Of Fibrin Applications In Bone Tissue Enginementioning
confidence: 99%
“…Due to the conformational transformations of fibrinogen at these high temperatures, FMBs are highly haptotactic to various cell types, including osteogenic bone marrow-derived progenitors. 99,100 For bone tissue engineering studies, the obtained FMBs were incubated for 2 days in a suspension containing whole 97,98,101 Next, authors cultured FMB-MSCs constructs in osteogenic medium and obtained a bone-like structure which was implanted into a mouse skull defect. After 2 months, results showed that defects filled with bone-like tissue had a Ca/P ratio similar to that of the native bone while no repair was seen in the control animals without implants or when the defect was filled with FMBs alone.…”
Section: Different Forms Of Fibrin Applications In Bone Tissue Enginementioning
confidence: 99%
“…26 In brief, after the sacrifice of male FSL rats, the tibias and femurs were removed and cleaned of connective tissue. Marrow was flushed out of the cut bones after removal of the epiphysis and suspended in Dulbecco's modified Eagle's medium (DMEM; Biological Industries, Beit Haemek, Israel) supplemented with 10% fetal bovine serum (Biological Industries), 100 units ml À1 of penicillin (Biological Industries), 100 mg ml À1 of streptomycin (Biological Industries) and 2 mM of L-glutamine (Biological Industries).…”
Section: Animalsmentioning
confidence: 99%